When identities collide: becoming founders in pastoralist Kenya - Delichte, Jody (Graduate School of Business (GSB), 2020)
There is an increasing number of entrepreneurship initiatives that aim to address extreme poverty, but we know little about how they shape founder identity and how diverse identities shape behavior. Although founder identity is a burgeoning field of study, theory is based primarily on research in developed country contexts. We know little about how founder identities emerge and change, and this gap is pronounced with respect to contexts of extreme poverty. I therefore explore how founder identities emerge and change in contexts of extreme poverty with a longitudinal study in a pastoralist community in Northern Kenya, where business itself is nascent, and impoverished pastoralists are in the early stages of learning basic business concepts. I conduct an inductive, qualitative study of 51 pastoralists over three years. Applying both social identity theory and identity theory lenses, this study identifies extant social and role identities that shape what it means to be a founder, as well as new identities introduced through business education and exposure, which conflict with extant identities. I identify three types of founder identity and develop a model illustrating the process through which they emerge based on varied responses to the identity conflict. Founders either maintain emphasis on extant identities, balance emphasis between some extant identities and some new identities, or transform to emphasize new identities, thus shaping who they become as a founder. When founders deviate from external expectations associated with extant identities, they engage in various forms of external identity work to increase acceptance of new behaviors and expectations and change perceptions of who they are as a founder. I further demonstrate that who one becomes as a founder is regulated by the degree of internalization and importance of extant identities that become part of what it means to be a founder in addition to other social identities held by the founder. My findings contribute to the literature on entrepreneurship in contexts of extreme poverty by providing a more nuanced conceptualization of founder identity in these contexts, including identification of three types of founder identity. I also contribute to both the literature on entrepreneurship in contexts of extreme poverty and founder identity theory more broadly by explaining the process through which founder identities emerge, introducing regulating identities as an explanation for variance in founder identity change, and bringing external identity work to the fore as a key process in founder identity construction and change. My findings also highlight the importance of applying an identity lens to the study of entrepreneurship initiatives in contexts of extreme poverty. I outline future research directions, as well as practical implications for organizations that aim to stimulate and develop entrepreneurship in contexts of extreme poverty through education and access to resources.